TONEEL CLUB KELIMUTU (PERJUANGAN KEMERDEKAAN SUKARNO DARI ENDE-FLORES 1934-1938 - Fatma Wati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
ABSTRACT The Dutch East Indies government saw the need to move Sukarno to a distant place and separate him from his political colleagues so that Sukarno could not carry out activities within his political parties that tried to oppose the Government. Ende, who is in the middle of Flores Island, is considered to be a suitable location to alienate this respected political figure. With a historical approach, this paper seeks to reveal the history of the formation of the Kelimutu Toneel Club which was formed by Soekarno during his exile in Ende from 1934-1938. The results showed that even though he was in a remote place and far from Java, Soekarno still fueled his fighting spirit by forming the Kelimutu Toneel Club, a drama group with a mission of struggle and a spirit of revolution. The drama was written by Soekarno himself and the actors were Soekarno's friends whom he met during his exile in Ende. With the help of his wife, Inggit Garnasih, adopted daughters of Ratna Juami and Kartika, as well as his mother-in-law Amsi and his friends, Soekarno succeeded in bringing up the theme of struggle in every performance of Toneel Club Kelimutu. Keywords: Toneel Club Kelimutu, Sukarno, Ende